Aluminum alloy brazing plate and method for manufacturing the same
By adopting aluminum alloy brazed plates with specific chemical components and Mg distribution, the problem of poor aluminum brazing without using flux is solved, and the brazing effect with high efficiency and excellent quality is achieved, and the structure of the brazing plate is simplified.
Patent Information
- Application Number
- CN202080097182.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2020-03-30
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2040-03-30
AI Technical Summary
In the prior art, when the aluminum is brazed without flux, there is a problem of poor brazing, especially in an inactive gas atmosphere or vacuum, the brazed plate has a complex structure and low productivity.
The aluminum alloy brazing plate with a core material composed of an aluminum alloy containing more than 0.40% and less than 2.50% and a brazed material laminated structure composed of an aluminum alloy containing more than 6.0% and more than 13.0% and less than 0.010% and less than 0.050% and less than Bi, is used, and the Mg distribution in the brazing material is continuously reduced from the core material boundary surface to the outermost surface.
The quality and efficiency of brazing are improved without using flux. The brazing plate has good brazing properties and a simple structure, which avoids the problems of low productivity and increased material costs.
Smart Images

Figure CN115151352B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an aluminum alloy brazing sheet for brazing aluminum in an inert gas atmosphere or in a vacuum without using a flux, and a method for producing the same. Background Art
[0002] Brazing is widely used as a method for joining products with multiple fine joints, such as aluminum heat exchangers or mechanical parts. In order to braze aluminum materials (including aluminum and aluminum alloys. The same applies below), it is necessary to destroy the oxide film on the surface of the aluminum material and bring the molten brazing filler metal into contact with the base material or molten brazing filler metal of the joining object. As methods for destroying the oxide film, there are methods using flux and methods of heating in a vacuum. In addition, brazing of aluminum materials often uses a brazing plate having a core material and a brazing filler metal provided on at least one side of the core material.
[0003] However, in the flux brazing method, that is, the brazing method using flux to destroy the oxide film, the material cost of the flux and the operation cost in the process of applying the flux become factors that increase the manufacturing cost of aluminum products.
[0004] In order to avoid the above-mentioned problems associated with the use of flux, the so-called vacuum brazing method is sometimes used, in which the flux is not applied to the surface of the intended joint portion and the brazing is performed in a vacuum, depending on the use of the aluminum product. However, compared with the flux brazing method, the vacuum brazing method has the problem of low productivity or the quality of the brazed joint being easily deteriorated. In addition, the brazing furnace used in the vacuum brazing method has higher equipment costs and maintenance costs than the general brazing furnace.
[0005] Therefore, a so-called flux-free brazing method has been proposed, in which the brazing is performed in an inert gas atmosphere without applying a flux on the surface of the intended joining portion. The brazing sheet used in the flux-free brazing method has an element that weakens or destroys the oxide film in the intended joining portion in at least one layer of its laminated structure. As such an element, Mg (magnesium) is often used.
[0006] However, Mg is easily oxidized. Therefore, when Mg is simply added to the brazing filler metal, a film of MgO is formed on the surface of the brazing filler metal during brazing heating, which may lead to deterioration of brazing properties. In order to avoid such problems, a technical solution has been proposed in which an intermediate material containing Mg is placed between the core material and the brazing filler metal in the brazing sheet, and Mg is diffused from the intermediate material to the surface of the brazing filler metal by heating during brazing.
[0007] For example, Patent Document 1 discloses a brazing plate comprising: a core material; an intermediate brazing material layer, the intermediate brazing material layer being composed of an Al-Si-Mg alloy containing 1 mass % or more and less than 4 mass % of Si (silicon) and 0.1 to 5.0 mass % of Mg (magnesium), and being coated on the core material; and an outermost brazing material layer, the outermost brazing material layer being composed of an Al-Si alloy containing 4 to 12 mass % of Si, and being coated on the intermediate brazing material layer.
[0008] Prior art literature
[0009] Patent Literature
[0010] Patent Document 1: Japanese Patent No. 6055573 Summary of the invention
[0011] Problems to be solved by the invention
[0012] However, when brazing is performed using the brazing sheet of Patent Document 1, the brittleness of the oxide film caused by Mg does not occur until the Mg in the intermediate brazing material layer reaches the surface of the brazing sheet. Moreover, since Mg moves in the solid intermediate brazing material layer and the outermost surface brazing material layer, it takes a relatively long time to reach the surface of the brazing sheet. Therefore, the brazing sheet may cause the above-mentioned poor brazing when, for example, the thickness of the brazing material is thick or the heating rate is fast.
[0013] In addition, when an intermediate material is interposed between the core material and the brazing material as in the brazing sheet of Patent Document 1, the number of layers contained in the brazing sheet increases compared to the case where the intermediate material is not provided, so the structure of the brazing sheet becomes more complicated. In addition, the increase in the number of layers of the brazing sheet may lead to a decrease in productivity or an increase in material cost.
[0014] The present invention has been made in view of the above background, and provides a brazing sheet having excellent brazing properties when brazing without using flux and having a simple structure, and a method for producing the same.
[0015] Technical solutions to solve problems
[0016] One embodiment of the present invention is an aluminum alloy brazing sheet that can be used for brazing without using a flux, the aluminum alloy brazing sheet comprising:
[0017] a core material composed of an aluminum alloy containing 0.40 mass % or more and 2.50 mass % or less of Mg (magnesium); and
[0018] a brazing filler metal composed of an aluminum alloy containing Mg, 6.0 mass % or more and 13.0 mass % or less of Si (silicon) and 0.010 mass % or more and 0.050 mass % or less of Bi (bismuth), laminated on at least one surface of the core material and exposed on the outermost surface,
[0019] The brazing filler metal has a Mg distribution in which the Mg concentration continuously decreases from the boundary surface with the core material as it approaches the outermost surface.
[0020] The Mg concentration at a position whose depth from the outermost surface is 1 / 8 of the thickness of the brazing material is 0.080 mass % or less, and
[0021] The Mg concentration at a position where the depth from the outermost surface is 7 / 8 of the thickness of the brazing material is 15 to 45% of the amount of Mg in the core material.
[0022] Effects of the Invention
[0023] The aluminum alloy brazing plate (hereinafter referred to as "brazing plate") comprises the core material and the brazing filler metal laminated on at least one surface of the core material and exposed on the outermost surface. In addition, the Mg in the brazing filler metal is distributed in a manner that the Mg concentration continuously decreases as it gradually approaches the outermost surface of the brazing plate from the boundary surface with the core material. Moreover, the Mg concentration at a position where the depth from the outermost surface is 1 / 8 of the thickness of the brazing filler metal and the Mg concentration at a position where the depth from the outermost surface is 7 / 8 of the thickness of the brazing filler metal are respectively within the specific range.
[0024] Mg in the brazing filler metal lowers the solidus temperature of the brazing filler metal, and can generate molten brazing filler metal at a relatively low temperature. Furthermore, by forming the above-mentioned specific Mg distribution in the brazing filler metal in advance, Mg can be quickly supplied to the outermost surface of the brazing plate while suppressing oxidation of Mg during brazing.
[0025] Furthermore, by rapidly supplying Mg to the outermost surface and generating molten brazing material at a relatively low temperature, the formation speed of the fillet in the intended joining portion can be accelerated. As a result, the brazing property in the so-called flux-free brazing method or vacuum brazing method performed in an inert gas atmosphere without using a flux can be improved.
[0026] In addition, the brazing sheet forms the specific Mg distribution in a single layer such as the brazing material, thereby avoiding an increase in the number of layers contained in the brazing sheet, thereby avoiding complication of the structure of the brazing sheet, and avoiding a decrease in productivity or an increase in material cost.
[0027] As a result of the above, according to the above aspect, it is possible to provide a brazing sheet having good brazing properties when brazing without using flux and having a simple structure. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is a partial cross-sectional view showing a main portion of the brazing sheet in Example 1.
[0029] Figure 2 This is a side view of a test body used in the gap filling test of Example 1. DETAILED DESCRIPTION
[0030] In the brazing sheet, the brazing material is laminated on at least one side of the core material. That is, the brazing sheet may have a double-layer structure consisting of the core material and the brazing material laminated on one side of the core material, or may have a three-layer structure consisting of the core material and the brazing material laminated on both sides of the core material.
[0031] In addition, the brazing plate may have a multilayer structure of three or more layers, wherein the multilayer structure of three or more layers comprises a core material, a brazing filler metal laminated on one side of the core material, and a layer composed of an aluminum alloy different from the core material and the brazing filler metal and laminated on the other side of the core material. The layer may be, for example, a sacrificial anode material or a second brazing filler metal having a chemical composition different from that of the brazing filler metal.
[0032] When the brazing material is stacked on one surface of the core material and the second brazing material is stacked on the other surface, the second brazing material may not have the specific Mg distribution. The second brazing material may have a different thickness from the first brazing material.
[0033] The thickness of the brazing plate can be appropriately set in the range of 0.050 to 2.0 mm, for example. In addition, the coverage rate of the brazing material in the brazing plate can be appropriately set in the range of 3 to 20%, for example. From the viewpoint of allowing Mg in the brazing material to reach the outermost surface of the brazing plate at an early stage, the coverage rate of the brazing material is preferably set to 3 to 10%.
[0034] The chemical components of the layers constituting the brazing sheet and the reasons for their limitations are described below.
[0035] (core material)
[0036] The core material of the brazing sheet is composed of an aluminum alloy containing 0.40 mass % or more and 2.50 mass % or less of Mg. The aluminum alloy constituting the core material may have a chemical composition containing 0.40 mass % or more and 2.50 mass % or less of Mg, and the balance being Al (aluminum) and inevitable impurities. In addition, in addition to Mg as an essential component, the aluminum alloy constituting the core material may also contain Fe (iron), Mn (manganese), Si (silicon), Cu (copper), Zn (zinc), Ti (titanium), and Zr (zirconium) as optional components.
[0037] Mg: 0.40 mass% or more and 2.50 mass% or less
[0038] In the initial stage of brazing, that is, before the brazing filler metal melts, the Mg in the core material diffuses due to the brazing heating and moves from the core material to the solid brazing filler metal. Therefore, the total amount of Mg in the brazing filler metal gradually increases as the brazing progresses. Moreover, after the brazing progresses and the molten brazing filler metal is formed, the Mg in the molten brazing filler metal destroys the oxide film present in the intended joint portion. As a result, the brazing of the brazing plate and the object material can be performed without using flux.
[0039] By setting the amount of Mg in the core material to 0.40 mass % or more, the total amount of Mg in the molten brazing filler metal can be sufficiently increased, and the destruction of the oxide film can be promoted. As a result, the brazing property of the brazing sheet and the counterpart material can be improved. When the amount of Mg in the core material is less than 0.40 mass %, the total amount of Mg in the molten brazing filler metal is insufficient, which may lead to deterioration of the brazing property.
[0040] The higher the Mg content in the core material, the more the oxide film can be destroyed, and the brazing property can be further improved. From this viewpoint, the Mg content in the core material is preferably 0.50 mass % or more, and more preferably 0.60 mass % or more.
[0041] However, if the Mg content in the core material is too high, it is difficult to obtain an effect of improving brazing properties commensurate with the content. In addition, in this case, the formability of the brazing sheet may be deteriorated or erosion may occur due to the refinement of the core material grains. By setting the Mg content in the core material to 2.50% by mass or less, preferably to 1.50% by mass or less, it is possible to improve the brazing properties of the brazing sheet and the counterpart material while avoiding these problems.
[0042] ·Fe: 1.0 mass% or less
[0043] In the core material, as an optional component, Fe of less than 1.0 mass% may also be contained. Fe has the effect of improving the strength of the core material. However, if the content of Fe is too much, it is possible to cause the corrosion resistance of the core material to deteriorate. In addition, in this case, huge precipitates are easily formed in the core material, which may lead to a decrease in the formability of the brazing sheet. By setting the content of Fe to less than 1.0 mass%, more preferably to less than 0.70 mass%, further preferably to less than 0.40 mass%, and particularly preferably to less than 0.25 mass%, the strength of the core material can be further improved while avoiding these problems.
[0044] Mn: 1.80 mass % or less
[0045] In the core material, as an optional component, Mn may also be contained in an amount of 1.80% by mass or less. Mn has the effect of improving the strength of the core material. In addition, Mn has the effect of adjusting the potential of the core material and improving the corrosion resistance. From the viewpoint of further improving these effects, it is preferred that the content of Mn be set to 0.60% by mass or more. However, if the content of Mn is too much, cracks are easily generated in the core material during the manufacturing process of the brazing sheet. By setting the content of Mn to 1.80% by mass or less, and more preferably to 1.30% by mass or less, the deterioration of the manufacturability of the brazing sheet can be avoided, while further improving the strength and corrosion resistance of the core material.
[0046] ·Si: 1.0 mass % or less
[0047] The core material may contain Si in an amount of 1.0% by mass or less as an optional component. Si has the effect of improving the strength of the core material. However, if the content of Si is too much, the melting point of the core material is reduced, which may lead to deterioration of brazing properties. By setting the content of Si to 1.0% by mass or less, the strength of the core material can be further improved while avoiding deterioration of brazing properties.
[0048] Cu: 1.0 mass % or less
[0049] In the core material, as an optional component, Cu of less than 1.0 mass % may also be contained. Cu has the effect of improving the strength of the core material. In addition, Cu has the effect of adjusting the potential of the core material and improving the corrosion resistance. However, if the content of Cu is too much, intergranular corrosion is likely to occur. In addition, in this case, the melting point of the core material is reduced, which may lead to deterioration of brazing properties. By setting the content of Cu to less than 1.0 mass %, more preferably to less than 0.50 mass %, the strength and corrosion resistance of the core material can be further improved while avoiding these problems.
[0050] ·Zn: 3.0 mass % or less
[0051] In the core material, as an optional component, 3.0% by mass or less of Zn may also be contained. Zn has the effect of reducing the natural electrode potential of the core material. By reducing the natural potential of the core material, the core material can function as a sacrificial anode. However, if the content of Zn is too much, the natural electrode potential of the core material is excessively reduced, and the sacrificial corrosion protection effect may be impaired at an early stage. By setting the content of Zn to less than 3.0% by mass, more preferably to less than 1.5% by mass, the sacrificial corrosion protection effect based on the core material can be maintained for a longer period of time.
[0052] Ti: 0.20 mass% or less
[0053] In the core material, as an optional component, 0.20% by mass or less of Ti may be contained. Ti has the effect of corroding the core material in layers and inhibiting corrosion from proceeding in the depth direction. However, if the content of Ti is too much, huge precipitates are easily formed in the core material, which may lead to deterioration of the rolling properties during the manufacturing process of the brazing plate. In addition, in this case, it is possible to cause deterioration of the corrosion resistance of the core material. By setting the content of Ti to less than 0.20% by mass, and more preferably to less than 0.15% by mass, it is possible to more effectively inhibit the progress of corrosion in the depth direction of the core material while avoiding this problem.
[0054] Zr: 0.50 mass % or less
[0055] The core material may contain 0.50% by mass or less of Zr as an optional component. Zr has the effect of increasing the crystal grain size of the core material and inhibiting the occurrence of erosion. However, if the content of Zr is too high, cracks are easily generated in the core material during the manufacturing process of the brazing sheet. By setting the content of Zr to 0.50% by mass or less, more preferably to 0.20% by mass or less, it is possible to more effectively inhibit the occurrence of erosion while avoiding the deterioration of the manufacturability of the brazing sheet.
[0056] (Brazing material)
[0057] The brazing filler metal of the brazing sheet is composed of an aluminum alloy containing Mg, 6.0 mass % or more and 13.0 mass % or less of Si, and 0.010 mass % or more and 0.050 mass % or less of Bi. The aluminum alloy constituting the brazing filler metal may have a chemical composition containing Mg, 6.0 mass % or more and 13.0 mass % or less of Si, and 0.010 mass % or more and 0.050 mass % or less of Bi, with the remainder being Al (aluminum) and unavoidable impurities. In addition, in the aluminum alloy constituting the brazing filler metal, in addition to Mg and Si as essential components, Sr (strontium) and Sb (antimony) may also be contained as optional components.
[0058] ·Si: 6.0 mass % or more and 13.0 mass % or less
[0059] Si in the brazing filler metal has the effect of lowering the melting point of the brazing filler metal and generating molten brazing filler metal during brazing. By setting the Si content to 6.0 mass % or more, preferably 7.0 mass % or more, a sufficient amount of molten brazing filler metal is generated during brazing, and brazing of the brazing plate and the counterpart material can be performed. When the Si content in the brazing filler metal is less than 6.0 mass %, the amount of molten brazing filler metal is insufficient, which may lead to deterioration of brazing properties.
[0060] However, if the Si content in the brazing material is too much, the amount of core material dissolved during brazing becomes too much, and the strength of the core material after brazing may be reduced. In addition, in this case, coarse primary Si is easily formed in the brazing material, and molten holes may be easily generated during brazing heating. Furthermore, when hot rolling is performed during the manufacturing process of the brazing sheet, due to the presence of primary Si, the core material partially melts, which may cause rolling cracks. By setting the Si content in the brazing material to less than 13.0 mass%, preferably less than 12.0 mass%, a sufficient amount of molten brazing material can be generated while avoiding these problems.
[0061] Mg
[0062] The brazing filler metal contains Mg. The Mg in the brazing filler metal is distributed in a manner that the Mg concentration continuously decreases as the Mg concentration gradually approaches the outermost surface from the boundary surface with the core material. In addition, the Mg concentration at a position where the depth of the brazing sheet from the outermost surface is 1 / 8 of the thickness of the brazing filler metal is less than 0.080 mass %, and the Mg concentration at a position where the depth of the brazing sheet from the outermost surface is 7 / 8 of the thickness of the brazing filler metal is 15 to 45% of the Mg amount in the core material.
[0063] Here, "continuous" means that the Mg concentration distribution obtained by plotting the Mg concentration at each depth with the Mg concentration in the brazing material as the vertical axis and the depth from the outermost surface as the horizontal axis presents a smooth curve. For example, if the brazing material is composed of multiple layers with different Mg concentrations, the state in which the Mg concentration distribution presents a step-like shape is excluded from the concept of "continuous".
[0064] As described above, the Mg present in the brazing filler metal reaches the outermost surface of the brazing plate earlier than the Mg in the core material due to the brazing heating. The Mg can quickly destroy the oxide film present in the intended joining portion. In addition, the Mg in the brazing filler metal lowers the solidus temperature of the brazing filler metal, and can generate molten brazing filler metal from a relatively low temperature.
[0065] The brazing sheet can sufficiently reduce the amount of Mg present on the outermost surface of the brazing sheet by setting the Mg concentration at a position 1 / 8 of the thickness of the brazing material from the outermost surface to 0.080 mass % or less, thereby reducing the amount of MgO generated in the initial stage of brazing and avoiding deterioration of brazing properties.
[0066] When the Mg concentration in the specific position exceeds 0.080 mass%, Mg is oxidized in the initial stage of brazing, and a MgO film is easily formed on the outermost surface of the brazing plate. Moreover, the presence of the MgO film prevents the destruction of the oxide film present in the intended joining portion, which may lead to deterioration of brazing properties.
[0067] In addition, the brazing plate can make an appropriate amount of Mg quickly reach the outermost surface of the brazing plate in the initial stage of brazing by setting the Mg concentration at a position 1 / 8 of the thickness of the brazing material from the outermost surface to 15% or more, preferably 25% or more, and more preferably 30% or more. As a result, the oxide film present in the intended joint portion can be quickly destroyed. In addition, in this case, the solidus temperature of the brazing material can be appropriately lowered, and the formation speed of the weld leg can be accelerated. As a result, the brazing performance can be improved.
[0068] When the Mg concentration in the specific position is less than 15% of the Mg content in the core material, it is difficult to destroy the oxide film with the Mg present in the brazing material. In addition, in this case, since the effect of lowering the solidus temperature of the brazing material is low, the formation speed of the fillet may also be reduced. As a result, the brazing performance may be reduced.
[0069] From the viewpoint of further improving brazing properties, it is preferable to increase the amount of Mg present in the brazing material. However, when the amount of Mg present in the brazing material is too much, the amount of Mg reaching the outermost surface of the brazing plate in the initial stage of brazing is too much. Therefore, a film of MgO is easily formed on the outermost surface of the brazing plate, which may lead to deterioration of brazing properties. This problem can be avoided by setting the Mg concentration in the specific position to less than 45% of the Mg amount in the core material, preferably less than 40%.
[0070] Bi: 0.010 mass % or more and 0.050 mass % or less
[0071] The brazing filler metal contains Bi in an amount of 0.010 mass % or more and 0.050 mass % or less. Bi has the effect of inhibiting oxidation of the brazing sheet during brazing. The Bi in the brazing filler metal is concentrated to the outermost surface of the brazing sheet during brazing. By setting the Bi content to 0.010 mass % or more and 0.050 mass % or less, preferably to 0.010 mass % or more and 0.045 mass % or less, further preferably to 0.010 mass % or more and 0.040 mass % or less, and particularly preferably to 0.010 mass % or more and 0.035 mass % or less, it is possible to inhibit the formation of a dense oxide film due to heating during brazing and further improve the brazing property. Bi is particularly effective when brazing is performed in an inert gas atmosphere with a relatively high oxygen concentration, such as when the oxygen concentration in the brazing atmosphere is about 50 to 500 ppm by volume.
[0072] ·Sr: 0.10% or less, Sb: 0.10% or less
[0073] The brazing filler metal may contain one or both of Sr: 0.10% or less and Sb: 0.10% or less as optional components. These elements have the effect of refining the structure of the joint formed after brazing, that is, the solidified brazing filler metal, and improving the bonding strength. From the viewpoint of further improving the effect of improving the bonding strength brought about by these elements, the content of Sr is preferably 0.0030% by mass or more and the content of Sb is preferably 0.0040% by mass or more.
[0074] However, if the contents of Sr and Sb are too much, it is difficult to obtain the effect of improving the brazing property commensurate with the contents of these elements. By setting the content of Sr to 0.10 mass % or less, preferably to 0.050 mass % or less, the effect of improving the brazing property commensurate with the content of Sr can be obtained. Similarly, by setting the content of Sb to 0.10 mass % or less, preferably to 0.050 mass % or less, the effect of improving the brazing property commensurate with the content of Sb can be obtained.
[0075] (Sacrificial anode material)
[0076] The brazing plate comprises: a core material; a brazing filler metal, which is laminated on one surface of the core material; and a sacrificial anode material, which is composed of pure aluminum or an aluminum alloy containing Zn: 8.0% by mass or less, and is laminated on the other surface of the core material. In this case, the corrosion resistance of the aluminum product after brazing can be further improved by the sacrificial corrosion protection effect of the sacrificial anode material. In addition, the above-mentioned "pure aluminum" refers to an aluminum material with an Al purity of 99.00% by mass or more.
[0077] When an aluminum alloy containing Zn is used as a sacrificial anode material, the aluminum alloy may have a chemical composition containing, for example, more than 0 mass % and less than 8.0 mass % Zn, with the remainder being Al and inevitable impurities. From the viewpoint of further improving the effect of improving the corrosion resistance of the aluminum product, the Zn content is more preferably 0.50 mass % or more.
[0078] On the other hand, if the Zn content is too high, the potential of the sacrificial anode material is excessively reduced, and corrosion may be accelerated. By setting the Zn content to 8.0 mass % or less, more preferably to 5.0 mass % or less, the sacrificial corrosion protection effect can be further improved while avoiding this problem.
[0079] The aluminum alloy constituting the sacrificial anode material may also contain one or both of In (indium): 0.0050-0.100 mass % and Sn (tin): 0.0050-0.100 mass %. In and Sn, like Zn, have the effect of reducing the natural electrode potential of the sacrificial anode material. However, if the content of In and Sn is too high, the natural electrode potential of the sacrificial anode material is excessively reduced, which may lead to the deterioration of its own corrosion resistance.
[0080] By setting the content of In and Sn to 0.0050 mass % or more, more preferably to 0.010 mass % or more, the sacrificial corrosion protection effect brought by the sacrificial anode material can be further improved. In addition, by setting the content of In and Sn to 0.100 mass % or less, more preferably to 0.050 mass % or less, respectively, the sacrificial corrosion protection effect can be obtained while avoiding the degradation of its own corrosion resistance.
[0081] The sacrificial anode material may also contain Mg: 3.0 mass % or less. The Mg in the sacrificial anode material can destroy the oxide film present on the surface of the sacrificial anode material. Therefore, by using an aluminum alloy containing Mg as the sacrificial anode material, the wettability of the sacrificial anode material to the molten brazing material can be improved, and the sacrificial anode material and other parts can be brazed.
[0082] However, if the Mg content in the sacrificial anode material is too high, Mg oxides are formed on the surface of the sacrificial anode material, which may lead to deterioration of brazing performance. By setting the Mg content in the sacrificial anode material to 3.0 mass % or less, more preferably to 1.5 mass % or less, the formation of Mg oxides can be suppressed while improving brazing performance.
[0083] The sacrificial anode material may also contain one or more of Mn: 2.0 mass % or less, Mg: 3.0 mass % or less, Si: 1.5 mass % or less, Cu: 1.0 mass % or less, Ti: 0.3 mass % or less, Zr: 0.3 mass % or less, and Cr: 0.3 mass % or less. These elements have the effect of increasing the strength of the brazing sheet by forming intermetallic compounds in the aluminum matrix phase or dissolving in the aluminum matrix phase.
[0084] (Second solder)
[0085] The brazing sheet may include: a core material; the brazing filler metal, which is laminated on one surface of the core material; and a second brazing filler metal, which is composed of an aluminum alloy different from the core material and the brazing filler metal and is laminated on the other surface of the core material. As the aluminum alloy constituting the second brazing filler metal, a well-known Al-Si alloy can be used.
[0086] The brazing sheet of the above aspect can be produced by, for example, the following production method.
[0087] First, a cladding block is prepared, which has a core material block and a brazing material block. The core material block has the chemical composition of the core material, and the brazing material block is composed of an aluminum alloy containing 6.0 mass% to 13.0 mass% Si and 0.010 mass% to 0.050 mass% Bi, and overlaps with the core material block.
[0088] The cladding material is produced by hot-rolling the cladding block and joining the layers constituting the cladding block.
[0089] Next, the clad material is cold rolled one or more times, and the clad material is heated one or more times at least between the cold rolling passes and after the final pass to diffuse Mg, thereby forming a Mg distribution in the brazing material.
[0090] The cladding block can be a laminated structure corresponding to the structure of the desired brazing plate. For example, in the case of making a brazing plate having a three-layer structure with a core material and the brazing material laminated on both sides of the core material, the brazing material blocks are overlapped on both sides of the core material block to make a cladding block with a three-layer structure.
[0091] The hot rolling of the cladding block can be performed, for example, under the condition that the rolling start temperature is 400 to 500°C. In addition, in the hot rolling, it is preferable to roll the cladding material so that the plate thickness becomes thicker than 200% of the desired thickness of the brazing plate. In the hot rolling, the Mg in the core material block diffuses into the brazing material block during the rolling, and sometimes an extremely thin Mg diffusion layer is formed in the brazing material of the cladding material.
[0092] By making the thickness of the cladding material thicker than 200% of the thickness of the brazing sheet, the Mg diffusion layer is compressed in the thickness direction during the subsequent cold rolling, and the thickness of the Mg diffusion layer can be made to be negligible. As a result, the desired Mg distribution can be formed with high precision during the subsequent heat treatment. When the thickness of the cladding material is less than 200% of the thickness of the brazing sheet, the compression amount of the Mg diffusion layer during the subsequent cold rolling is likely to be insufficient. If the compression amount of the Mg diffusion layer is insufficient, in the subsequent heat treatment, it is necessary to diffuse Mg from the core material to the brazing material while considering the thickness of the Mg diffusion layer. As a result, the setting of the heat treatment conditions may become complicated.
[0093] After the cladding material is produced by hot rolling, the cladding material is cold rolled one or more times, and the cladding material is heated one or more times between the cold rolling passes and at least one time after the final pass to diffuse Mg. That is, when the cladding material is cold rolled one time to obtain the desired thickness, the cladding material can be heated after the cold rolling to form the Mg distribution. In addition, when the cladding material is cold rolled two or more times to obtain the desired thickness, for example, the heating can be performed between any passes or after the final pass. Furthermore, the heating can also be performed at two or more time points between the cold rolling passes and after the final pass.
[0094] The heating for diffusing Mg may also serve as a heat treatment for adjusting mechanical properties such as so-called intermediate annealing or final annealing, or may be performed as a separate process from these heat treatments.
[0095] When Mg is diffused from the core material into the brazing material, it is preferred that the value of D represented by the following formula (1) is 1.0×10 -15 ~3.0×10 -9 The coating material is heated under the conditions of 3.0×10 -11 ~3.0×10 -9 The coating material is heated under conditions of.
[0096] [Mathematical formula 1]
[0097]
[0098] Wherein, n in the formula (1) is the number of heating times during which the thickness of the cladding material is within the range of 100 to 200% of the thickness of the brazing sheet, and Th k is the thickness of the brazing material of the coating material during the kth heating (m), R is the gas constant (J / mol·K), t k0 is the time when the temperature of the coating material exceeds 50° C. during the kth heating, t k1 is the time when the temperature of the coating material during the kth heating drops to 50° C., and T(t) is the temperature (K) of the coating material at time t. In addition, the time differential dt in the formula (1) is expressed in seconds.
[0099] The value of D in the formula (1) is the total value of the diffusion distance of Mg during heating when the thickness of the cladding material is in the range of 100 to 200% of the thickness of the brazing plate. By setting the value of D in the specific range, Mg can be appropriately diffused into the brazing material, and the specific Mg distribution can be more reliably formed.
[0100] In the manufacturing method of the above embodiment, the surface of the brazing plate may be etched with acid as needed. By etching, the oxide film formed by heating during hot rolling or heating during Mg diffusion can be weakened or removed. As a result, the brazing property of the brazing plate can be further improved.
[0101] The etching period is not particularly limited as long as it is between hot rolling and brazing with the brazing plate. For example, etching can be performed on the cladding plate after hot rolling, or etching can be performed on the cladding plate in the middle of cold rolling. In addition, etching can also be performed after the heat treatment performed after hot rolling and before the cold rolling is completely completed.
[0102] In addition, the brazing sheet may be etched immediately after the above-mentioned heating and cold rolling are all completed. Furthermore, after the above-mentioned heating and cold rolling are all completed, the brazing sheet may be stored in a state with the above-mentioned oxide film, and the etching may be performed immediately before brazing. If the above-mentioned oxide film is weakened or removed during brazing, the brazing property of brazing using the brazing sheet can be improved.
[0103] As the acid used for etching the brazing plate, for example, aqueous solutions of sulfuric acid, hydrochloric acid, nitric acid, phosphoric acid, hydrofluoric acid, etc. can be used. These acids can be used alone or in combination of two or more. From the viewpoint of more effectively removing the oxide film, as the acid, a mixed aqueous solution containing hydrofluoric acid and an acid other than hydrofluoric acid is preferably used, and a mixed aqueous solution of hydrofluoric acid and sulfuric acid or a mixed aqueous solution of hydrofluoric acid and nitric acid is more preferably used.
[0104] The etching amount during etching is preferably 0.05 to 2 g / m 2 By setting the etching amount to 0.05 g / m 2 More preferably, it is 0.1 g / m 2 As described above, the oxide film on the surface of the brazing sheet can be sufficiently removed, and the brazing performance can be further improved.
[0105] From the perspective of improving the brazing performance of the brazing sheet, there is no upper limit to the etching amount. However, if the etching amount is too much, it may be difficult to obtain an effect of improving the brazing performance commensurate with the processing time. 2 Below, more preferably set to 0.5g / m 2 This problem can be avoided as follows.
[0106] The brazing sheet can be used as either a flux-free brazing method or a vacuum brazing method. When the brazing sheet is used and brazing is performed by a flux-free brazing method, the oxygen concentration in the inert gas as the brazing atmosphere is preferably set to 20 volume ppm or less, and more preferably set to 10 volume ppm or less. In this case, oxidation of Mg and the like caused by oxygen can be suppressed, and brazing properties can be further improved.
[0107] Example
[0108] The brazing sheet and the method for producing the same are described below in their embodiments. The brazing sheet and the method for producing the same according to the present invention are not limited to the embodiments described below, and the structure may be modified as appropriate within the scope of the present invention.
[0109] In this example, core materials having chemical compositions shown in alloy symbols C1 to C14 in Table 1, brazing materials having chemical compositions shown in alloy symbols F1 to F8, and sacrificial anode materials having chemical compositions shown in alloy symbols L1 to L4 are used. It should be noted that the symbol "-" in Table 1 indicates that the element is not actively added and the content does not exceed the content as an unavoidable impurity. In addition, the symbol "Bal." in the table indicates the balance.
[0110] [Table 1]
[0111]
[0112] (Example 1)
[0113] like Figure 1 As shown in FIG. 1 , this example is an example of a double-layer brazing sheet 1 composed of a core material 11 and a brazing material 12 stacked on one side of the core material 11 (see FIG. 1 ). Figure 1 ). The method for producing the brazing plate 1 of this example is as follows. First, a core material block having the chemical composition (alloy symbols C1 to C14) shown in Table 1 is produced by continuous casting. Next, the core material block is subjected to face cutting to make the thickness of the core material block a predetermined thickness.
[0114] In addition, different from the core material block, the brazing material block having the chemical composition shown by the alloy symbols F1 to F8 in Table 1 and the sacrificial anode material block having the chemical composition shown by the alloy symbols L1 to L4 were produced by continuous casting. Then, the brazing material block and the sacrificial anode material block were hot-rolled to a predetermined thickness.
[0115] The core material blocks, brazing material blocks and sacrificial anode material blocks thus obtained were stacked in the combinations shown in Tables 2 and 3 to produce cladding blocks. The obtained cladding blocks were hot rolled and the stacked blocks were joined to produce cladding materials having a thickness of 3.0 mm.
[0116] Next, the clad material is subjected to multiple passes of cold rolling so that the thickness of the clad material becomes the value shown in Table 2 and Table 3. Then, after the final pass of cold rolling, the clad material is heated under heating conditions such that the value of D in the above formula (1) becomes the value shown in Table 2 and Table 3. In addition, the holding temperature during the heating can be selected from the range of 350 to 450° C., for example. In addition, the holding time can be selected from the range of 1 to 24 hours, for example. Thus, test materials 1 to 24 and 51 to 65 shown in Table 2 and Table 3 can be obtained.
[0117] Mg distribution in solder
[0118] The following method can be used to evaluate the Mg distribution in the brazing filler metal 12 of each test material. First, each test material is cut along the plate width direction, and the exposed cross section is mirror-polished. Figure 1 As shown, the depth of the randomly selected test material from the outermost surface 111 is the thickness t of the solder 12 f The analysis position of 3 points of 1 / 8 P 1 / 8 At each of these analysis positions P 1 / 8 Point analysis was performed using EPMA (electron probe microanalyzer) to measure the concentration of each analysis position P. 1 / 8 Then, each analysis position P 1 / 8 The average Mg concentration in the brazing material is set to be the Mg concentration c at a position where the depth from the outermost surface 121 is 1 / 8 of the thickness of the brazing material. 1 / 8 The Mg concentration c at this location in each test material 1 / 8 As shown in Table 2 and Table 3.
[0119] In addition, by changing the position of the point analysis by EPMA to the analysis position P where the depth from the outermost surface 121 of the test material is 7 / 8 of the thickness of the brazing material, 7 / 8 The same evaluation as above is performed, thereby obtaining the Mg concentration c at a position where the depth from the outermost surface is 7 / 8 of the solder thickness. 7 / 8 The Mg concentration c at this location in each test material 7 / 8 As shown in Table 2 and Table 3. In Table 2 and Table 3, the Mg concentration c at the above position of each test material is 7 / 8 The Mg concentration c at the location is recorded together with its own value. 7 / 8 Ratio (%) to the amount of Mg in the brazing filler metal.
[0120] ·Brazing evaluation based on gap filling test
[0121] By performing a gap filling test, the brazing properties of each test material can be evaluated. Figure 2 As shown, the test body 2 used in the gap filling test has a horizontal plate 21 taken from the test material and a vertical plate 22 arranged on the brazing material 12 of the horizontal plate 21. The vertical plate 22 is arranged in a direction orthogonal to the horizontal plate 21. In addition, one end 221 of the vertical plate 22 in the long side direction is in contact with the brazing material 12 of the horizontal plate 21. It should be noted that the width of the horizontal plate 21 in this example is 25 mm and the length is 60 mm. In addition, the vertical plate 22 is an aluminum plate made of JIS A3003 alloy with a width of 25 mm, a length of about 55 mm, and a thickness of 1 mm.
[0122] The spacer 23 is interposed between the other end 222 of the vertical plate 22 in the longitudinal direction and the horizontal plate 21. Thus, a gap S is formed between the horizontal plate 21 and the vertical plate 22, which gradually expands from the one end 221 of the vertical plate 22 toward the spacer 23 side. It should be noted that the spacer 23 in this example is specifically a stainless steel round wire with a diameter of 2.0 mm, and is arranged at a position 55 mm away from the position (one end 221) where the vertical plate 22 and the horizontal plate 21 abut.
[0123] For the test bodies 2 using test materials 1 to 19, 21 to 24, 51 to 59, and 61 to 65, the test bodies 2 were assembled after the horizontal plate 21 and the vertical plate 22 were degreased. In addition, for the test bodies 2 using test materials 20 and 60, the horizontal plate 21 and the vertical plate 22 were degreased and etched with acid in sequence, and then the test bodies 2 were assembled. Then, the test bodies 2 were brazed. It should be noted that for any of the test bodies, flux was not applied before brazing.
[0124] The brazing of the test body was performed using a nitrogen furnace. The atmosphere in the furnace was set to a nitrogen atmosphere with an oxygen concentration of 10 volume ppm or less. In addition, the brazing heating was performed by raising the temperature of the test body to 600°C and then maintaining the temperature of 600°C for 3 minutes. After the brazing heating was completed, the test body was slowly cooled in the furnace until the temperature dropped to a certain level, and then the test body was taken out of the furnace.
[0125] In the gap filling test, the length L and shape of the fillet 120 formed after brazing can be used to determine the gap filling performance. Figure 2) to evaluate the brazing property. In the "Length of Weld Leg" column in Table 2 and Table 3, the result of brazing the three test bodies 2 is that when the average length L filled with brazing material in the gap S is more than 25 mm, it is recorded as "A+", when the weld leg is more than 15 mm and less than 25 mm, it is recorded as "A", and when the weld leg is less than 15 mm, it is recorded as "B". In addition, in the "Shape of Weld Leg" column in the table, when the width of the weld leg is uniform and evenly formed on both sides of the vertical plate 22, it is recorded as "A", and when the width of the weld leg is uneven or only formed on one side of the vertical plate 22, it is recorded as "B".
[0126] In the evaluation of brazeability, when the length of the weld leg is "A+" or "A" and the shape of the weld leg is "A", it is judged as passing due to excellent brazeability. On the other hand, when the length of the weld leg is "B" or the shape of the weld leg is "B", it is judged as failing due to poor brazeability.
[0127] [Table 2]
[0128]
[0129] [Table 3]
[0130]
[0131] As shown in Tables 2 and 3, the chemical compositions of the core material 11 and the brazing material 12 of the test materials 1 to 24 are within the specific ranges, and a boundary surface 122 (refer to Figure 1 ) and the Mg concentration continuously decreases as it approaches the outermost surface 121. The depth from the outermost surface 121 is the thickness t of the brazing material 12. f The Mg concentration at the position 1 / 8 of c 1 / 8 is 0.080 mass % or less, and the depth from the outermost surface 121 is the thickness t of the brazing material 12 f The Mg concentration at the 7 / 8 position c 7 / 8 It is 15 to 45% of the amount of Mg in the core material 11. Therefore, according to these test materials, the brazing property of brazing without using flux can be improved.
[0132] Among these test materials, the test material 20 was subjected to etching using an acid. Therefore, the test material 20 can improve the brazing property compared with the test material 14 having the same structure except that the etching was not performed.
[0133] In the test materials 51, 53, and 58, the Mg content in the core material is less than the specific range, so the amount of Mg diffused from the core material to the brazing material during brazing heating is likely to be insufficient. Therefore, when these test materials are used, brazing defects are more likely to occur than in the test materials 1 to 24.
[0134] In test materials 52, 54, 59 to 60, the Mg content in the core material is higher than the specific range, so the amount of Mg diffused from the core material to the brazing material during brazing heating is too large. Therefore, when these test materials are used, brazing defects are more likely to occur than in test materials 1 to 24.
[0135] Since the brazing material does not contain Bi in the test materials 55 to 57, the surface of the brazing plate is easily oxidized during the brazing heating. Therefore, when these test materials are used, brazing defects are more likely to occur than in the test materials 1 to 24.
[0136] In the case of the test material 61, the Si content in the brazing material was less than the above-mentioned specific range, so the brazing material was likely to be insufficient during brazing. Therefore, when the test material 61 was used, brazing defects were more likely to occur than in the test materials 1 to 24.
[0137] In the case of the test material 62, the Si content in the brazing material is higher than the specific range, so the core material is easily corroded by the molten brazing material during brazing. Therefore, when the test material 62 is used, the core material melts and brazing may not be possible.
[0138] In the case of the test material 63, since the core material does not contain Mg, diffusion of Mg from the core material to the brazing material does not occur. Therefore, the test material 63 cannot be brazed without using a flux.
[0139] In the test material 64, the Mg content in the core material is higher than that in the test materials 52, 54, and 59 to 60. Therefore, the grains of the core material are refined during brazing, which may cause corrosion.
[0140] In the case of the test material 65, since the value of D in the formula (1) is greater than the specific range, the amount of Mg reaching the surface of the brazing material tends to be excessive. Therefore, when the test material 65 is used, a dense film of MgO is formed on the outermost surface of the test material during brazing, which may lead to deterioration of the brazing property.
[0141] As can be understood from the results of the examples described above, by setting the chemical compositions of the core material and the brazing filler metal within the specific ranges and forming the specific Mg distribution within the brazing filler metal, a brazing sheet having excellent brazing properties without using flux can be obtained.
Claims
1. An aluminum alloy brazing plate, which can be used for brazing without using flux, The aluminum alloy brazing plate has: a core material composed of an aluminum alloy containing 0.40 mass % or more and 2.50 mass % or less of Mg; and a brazing filler metal composed of an aluminum alloy containing Mg, 6.0 mass % or more and 13.0 mass % or less of Si, and 0.010 mass % or more and 0.050 mass % or less of Bi, which is laminated on at least one surface of the core material and exposed on the outermost surface, The brazing filler metal has a Mg distribution in which the Mg concentration continuously decreases from the boundary surface with the core material as it approaches the outermost surface. The Mg concentration at a position whose depth from the outermost surface is 1 / 8 of the thickness of the brazing material is 0.080 mass % or less, and The Mg concentration at a position where the depth from the outermost surface is 7 / 8 of the thickness of the brazing material is 15 to 45% of the amount of Mg in the core material.
2. The aluminum alloy brazing sheet according to claim 1, wherein: The brazing material further contains one or both of Sr: 0.10 mass % or less and Sb: 0.10 mass % or less.
3. The aluminum alloy brazing sheet according to claim 1 or 2, wherein: The core material further contains one or more of Fe: 1.0 mass % or less, Mn: 1.80 mass % or less, Si: 1.0 mass % or less, Cu: 1.0 mass % or less, Zn: 3.0 mass % or less, Ti: 0.20 mass % or less, and Zr: 0.50 mass % or less.
4. The aluminum alloy brazing sheet according to claim 1 or 2, wherein: The solder is laminated on both sides of the core material.
5. The aluminum alloy brazing sheet according to claim 1 or 2, wherein: The aluminum alloy brazing plate has: The core material; The brazing material is laminated on one surface of the core material; and The sacrificial anode material is composed of pure aluminum or an aluminum alloy containing Zn: 8.0 mass % or less and is laminated on the other surface of the core material.
6. The aluminum alloy brazing plate according to claim 5, wherein: The sacrificial anode material is composed of an aluminum alloy further containing one or more of 2.0 mass % or less of Mn, 3.0 mass % or less of Mg, 1.5 mass % or less of Si, 1.0 mass % or less of Fe, 1.0 mass % or less of Cu, 0.3 mass % or less of Ti, 0.3 mass % or less of Zr, and 0.3 mass % or less of Cr.
7. The aluminum alloy brazing plate according to claim 5, wherein: The sacrificial anode material is composed of an aluminum alloy further containing one or both of In: 0.0050 to 0.100 mass % and Sn: 0.0050 to 0.100 mass %.
8. A method for producing an aluminum alloy brazing sheet, which is the method for producing an aluminum alloy brazing sheet according to any one of claims 1 to 7, wherein: A cladding block is prepared having a core material block and a brazing material block, wherein the core material block has the chemical composition of the core material; the brazing material block is composed of an aluminum alloy containing 6.0 mass % or more and 13.0 mass % or less of Si and 0.010 mass % or more and 0.050 mass % or less of Bi, and overlaps with the core material block, The cladding material is produced by hot-rolling the cladding block and joining the layers constituting the cladding block. The clad material is cold rolled one or more times, and the clad material is heated one or more times at least between the cold rolling passes and after the final pass to diffuse Mg, thereby forming the Mg distribution in the brazing material.
9. The method for manufacturing an aluminum alloy brazing sheet according to claim 8, wherein: When Mg is diffused from the core material into the brazing material, the value of D represented by the following formula (1) is 1.0×10 -15 ~3.0×10 -9 heating the coating material under the conditions of , Wherein, n in the formula (1) is the number of heating times during which the thickness of the cladding material is within the range of 100% to 200% of the thickness of the brazing sheet; Th k is the thickness of the brazing material of the coating material at the kth heating, in meters; R is the gas constant, in J / mol·K; t k0 is the time when the temperature of the coating material exceeds 50° C. during the kth heating; t k1 is the time point when the temperature of the coating material is lower than 50° C. during the kth heating; T(t) is the temperature of the coating material at time t, in K.
10. The method for producing an aluminum alloy brazing sheet according to claim 8 or 9, wherein: The surface of the cladding material is etched using an acid during a period from after the hot rolling to when the brazing sheet is used for brazing.
11. The method for manufacturing an aluminum alloy brazing sheet according to claim 10, wherein: The etching amount of the etching is 0.05 to 2 g / m 2 .
Citation Information
Patent Citations
Cassette recorder
JP1985055573A
Aluminum alloy brazing sheet for heat exchangers and aluminum alloy brazed object for heat exchangers
CN102414332A
Brazing method for aluminum alloy brazing sheet
JP2018099726A